Exports, Inflation, and Growth - Gylfason, Thorvaldur (IMF Working Papers; Working Paper ;, 1997)
This paper identifies some of the main determinants of exports and economic growth in cross-sectional data from the World Bank, covering 160 countries in the period 1985-1994. First, the linkages between the propensity to export and population, per capita income, agriculture, primary exports, and inflation are studied by statistical methods. Then, the relationship between economic growth and some of the above-mentioned determinants of exports and investment are scrutinized the same way. The main conclusion is that, in the period under review, high inflation and an abundance of natural resources tended to be associated with low exports and slow growth.